FATWA MAJELIS ULAMA INDONESIA (MUI): TENTANG ALIRAN AHMADIYAH - Khoiruddin Nasution (Millah: Journal of Religious Studies, 2008)
At the end of 2007 and at the beginning of 2008, the issue of Ahmadiyah again becomes an important issue in Indonesia. Similar issue has been appeared in 1980 and produced a fatwa on it by Religious Council of Indonesia (MUI). This short paper describes basic reason of why Muslim majority in Indonesia oppose the existence of Ahmadiyah. To analyze the problem, the author utilizes the theory of levelling of the Islamic Teaching. Nasr Hamid Abu Zaid, for example, levels Islamic teaching into three levels; the original text of Islam, interpretation, and practiced by Muslims. Similar theory was formulated by Abdullah Saeed. The result is that the basic reason of the opposing of Indonesian Muslim to the existence of Ahmadiyah is its belief of the status of Mirza Ghulam Ahmad as a prophet. Since, according to the belief of Muslim majority, Muhammad SAW is the last prophet. Therefore, the best way to solve the problem is a declaration or a recognition that Ahmadiyah is out of Islam. This solution in fact has been offered by the Ministry of Religious Affairs of Indonesia.